The Influence of Implementation of the Regional Government Information System and the Government Internal Control System on Corruption (A Case Study on Regional Work Unit of Bandung Regency Government) - Yulianty, Dhea; Silviana, Silviana (Journal of Accounting and Finance Management, 2025)
This study aims to determine the effect of the Implementation of Local Government Information Systems and Government Internal Control Systems on Corruption (Case Study on the Regional Government Work Unit of Bandung Regency). The factors tested in this study are the Application of Local Government Information Systems and Government Internal Control Systems as independent variables and Corruption as the dependent variable. The research method used is quantitative. The data collection method used was a questionnaire. The data analysis technique used multiple linear regression analysis with the help of the Statistical Package for the Social Sciences 27 application. The results showed that the Application of Local Government Information Systems and Government Internal Control Systems had a negative effect on corruption.